Kualitas Pelayanan Pada Koperasi Laksmi Prasanthi Desa Tembok Kabupaten Buleleng - Santika, Kadek Ardi; Suwena, Kadek Rai (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to examine how far the quality of service between Expectations and Reality provided by Koperasi Laksmi Prasanthi Tembok Village Buleleng Regency. This type of research is descriptive qualitative with data collection methods in the form of questionnaires, but first tested validity and reliability. The number of samples used was 110 respondents. The sampling technique used Slovin's formula by taking the number of samples that must be representative so that the research results can be generalized and the calculation does not require a sample size table. The data analysis technique used is descriptive analysis. The results of this study indicate that of the 27 attributes studied, they have a total GAP value of -0.2. A total of 10 attributes have a positive GAP value where the quality of service is said to be quality and satisfying, while the other 17 attributes have a negative GAP value where the quality of service is said to be not quality and satisfying.